Combination effect of carbon nanofiber and ketjen carbon black hybrid nanofillers on mechanical, electrical, and electromagnetic interference shielding properties of chlorinated polyethylene nanocomposites. (15th September 2020) - Mondal, Subhadip; Ravindren, Revathy; Bhawal, Poushali; Shin, Beomsu; Ganguly, Sayan; Nah, Changwoon; Das, Narayan Ch
Abstract: Conductive hybrid nanofillers have become front facet of the recent research interest because of the scientific and techno-commercial significance of these materials. Herein, we report the fabrication of chlorinated polyethylene (CPE) nanocomposites filled with hybrid nanofiller of functionalized carbon nanofiber (FCNF) and nano-structured ketjen carbon black (K-CB) by using solution blending approach. Incorporation of hybrid nanofiller in CPE matrix led to a drastic enhancement in thermal, mechanical, and electrical properties. Proper distribution of hybrid nanofiller leads excellent electrical conductivity of 2.2 × 10 −2 S/cm and superior electromagnetic interference (EMI) shielding performance (33 dB) at 15 wt% hybrid nanofiller content in X-band frequency. Further, we addressed the serviceable performance in electrical conductivities and shileding performances after exposed to thermal-air ageing treatment. The novelty of this present work lies in the unique synergism arising from the combination of two nanofillers, which serves as outstanding EMI shield material as a capable candidate against EM pollutions. Graphical abstract: Solvent assisted hybrid nanocomposite shows excellent EMI shielding performance with tuned electrical conductivity. Image 1 Highlights: Hybrid nanofiller based chlorinated polyethylene nanocomposites are prepared by simple solution mixing method. Combination efficiency between CNF and K-CB was well understood by analyzing the electrical behavior and SE of nanocomposites. Hybrid nanocomposites show excellent serviceable performance after exposed to thermal-air ageing treatment. Proper distribution of hybrid nanofiller offers excellent electrical conductivity and EMI shielding effectiveness.